STUDI KUALITAS AIR LIMBAH PUSKESMAS DI KABUPATEN LOMBOK UTARA, PROVINSI NUSA TENGGARA BARAT - ENIDA FATMALIA; RIZKA DONNY AGUNG SAPUTRA (GANEC SWARA, 2021)
Health Center waste is all waste in the form of solid, liquid or gas originating from the activities of the Health Center which is likely to contain microorganisms, toxic and radioactive chemicals. The function of the Public health center is as the spearhead of health services in the community because it is in direct contact with the community. In addition to having a positive impact, Public health center also have a negative impact, namely pollution from waste that is produced if not handled properly. The purpose of this study was to determine the quality of waste water in the health center in North Lombok Regency and whether it meets the requirements based on Keputusan Menteri Lingkungan Hidup RI No.58 Tahun 1995 Tentang Baku Mutu Limbah Cair Bagi Kegiatan Rumah Sakit. The type of research is quantitative research with experimental methods, research subjects are all health centers in North Lombok Regency, data collection is carried out by taking wastewater samples at WWTP outlets in 3(three) Public health center. Samples were tested at the Biology and Chemistry Laboratory of Sekolah Tinggi Teknik Lingkungan (STTL) Mataram with 6 (six) test parameters, namely pH, BOD (Biological Oxygen Demand), COD (Chemical Oxygen Demand), TSS (Total Suspended Solid), Fatty Oil and Total coliforms. The results showed that the waste water of the Puskesmas in North Lombok Regency did not meet the quality standard requirements, namely the Senaru Public health center on the COD parameter with test results of 96 mg/L and the Total Coliform in all Public health center exceeded the quality standard of 10,000 MPN/100 ml